Pemberdayaan UMKM Batik Tulis Madura melalui Pelatihan Branding dan Digital Marketing - Nila Susanti; Moh. Muhajir (Transformative Service Journal, 2026)
Empowering Madura’s Hand-Written Batik UMKM through branding and digital marketing training aims to enhance the capacity of business actors to compete in both local and digital markets. This activity applies the Participatory Action Research (PAR) approach, actively involving UMKM in needs identification, program planning, implementation, and evaluation. Training covers brand identity strengthening, logo and packaging design, visual content production, and management of social media and marketplace platforms. The results show significant improvement in branding skills, content creation, and independent digital marketing management, with digital reach increasing by up to 120% within four weeks. These findings confirm the effectiveness of participatory approaches in promoting UMKM independence, product visibility, and competitiveness of Madura’s Hand-Written Batik, while contributing to sustainable local economic empowerment.